Theoretical Investigation of Ultraprecise Position Determination by Spatially Modulated Low-Coherence Interference Fringe in Optical Fiber Sensing - Xuezhi Zhang; Tiegen Liu; Junfeng Jiang; Kun Liu; Ming Feng; Shuang Wang; Jinde Yin (IEEE Photonics Journal, 2016)
A position determination method for low-coherence interference fringe in optical fiber sensing is proposed. This method can be used to measure displacement or length. An amplitude ratio curve is created from spatially modulated interference fringes. There is a one-to-one correspondence relationship between the peaks of the amplitude ratio curve and the extremes of the low-coherence interference fringe. The peak positions of the amplitude ratio curve only rely on the Fabry–Pérot (F-P) cavity length. In addition, the peaks of the amplitude ratio curve are very sharp, which can be easily identified. In the calculation of the amplitude ratio curve, the low-coherence interference fringe is spatially modulated by Pockels effects. The impacts of the modulated voltage on the sensing precision are analytically and numerically discussed. Compared with the envelop detection method, the position determination precision of low-coherence interference fringe is enhanced about 30 times by creating an amplitude ratio curve. This method can be widely employed in the sensing of all kinds of parameters that can be converted to displacement or length.